Green logistics strategy for South East Europe: to improve intermodality and establish green transport corridors - Beškovnik, Bojan; Twrdy, Elen (Transport, 2012)
This article describes the trend towards European green initiatives in the transport sector. The introduction of green logistics management and green policy in Europe has been analysed to understand better the positive impact of green policy on environment, society and economy. With the most recent EU initiatives in the field of green logistics, intermodality has become the platform for green logistics development in the EU. This stimulated a complete study of the case of South East Europe. The perspective of intermodal infrastructure development, the use of intermodality and the environmental impact of the transport sector has been analysed to build an appropriate model for a macro green logistics strategy for South East Europe, where Green transport corridors should be exposed as the main goal. In our proposal of a seven-pillar strategy, all parties, including governmental institutions, manufacturing industry and logistics operators, should take an active part, enabling industry to co-create a macro transport development in the region and to influence future legislation of green issues in the transport sector, with an aim to establish Green transport corridors till 2020. There is a strong need to regulate green logistics issues in the region of South East Europe; therefore, additional studies and proposals will be necessary in the future. First Published Online: 30 Mar 2012